Aplikasi Pemrograman Metode Elemen Hingga Pada Strukurbeam 2D Menggunakan Program C# - Rahman, Soleh; Afrizal, Efi; Nazaruddin, Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The application of structural analysis is increasingly having a very important role in its existence in today's engineering world. Nowadays there are so many applications that make problem analysis easier, especially in the field of mechanical engineering such as SOLIDWORKS, ANSYS, ABAQUS, INVENTOR and so on. However, these commercial applications are not only quite expensive but also have very strict licensing rules. Of course this raises a kind of concern for users of the application, especially mechanical engineering students at the University of Riau. These problems and reasons are what encourage the author's initiative and ideas to create a structural analysis application that can be used as an alternative for analyzing structural problems. There is no structural analysis application developed previously in the Department of Mechanical Engineering at the University of Riau, so as an initial stage, one of the analyzes that can be developed is a two-dimensional (2D) beam structure analysis that is subject to loading and is in an elastic state using triangular elements. or Constant Strain Element (CST). The development of the application program is based on the Finite Element Method (FEM). From the results of the research that has been done, it can be concluded that the results of calculations in the application that have been developed show the results of the close value after comparisons with the results of calculations on the popular commercial application, namely Abaqus.Keywords: Finite Element Method, structural analysis application, triangular element.